Web-Based Rapid Application Development (RAD) for Marketing of Ende Lio Traditional Bond Motif Woven Fabric - Neneng Awaliah; Akbar Hendra; Amran Amiruddin; Daud Daud; Akbar Iskandar (Ceddi Journal of Information System and Technology (JST), 2023)
The marketing of Ende Lio traditional bond motif ikat woven fabric predominantly relies on conventional market stalls. However, with the growing demand for diverse products derived from ikat weaving, such as garments, bags, tunics, and accessories, there is a need for a more efficient marketing strategy. This study aims to implement Rapid Application Development (RAD) and design a web-based marketing system for the Marketing of Ende Lio Traditional Bond Motif Woven Fabric to enhance accessibility and increase public awareness of the products. The objectives of this research include developing an intuitive and interactive web-based platform for marketing Ende Lio's woven ikat fabrics, improving the efficiency of the marketing process, ensuring a seamless user experience, and evaluating the system's impact on sales and customer satisfaction. The RAD methodology, renowned for its incremental and time-constrained software development approach, was employed. The design process involved the use of Use Case Diagrams, and unit testing was conducted to validate the functionality and performance of the application.